Minimally Invasive Discectomy and Decompression for Lumbar Spine using Tubular Retractor System: Technique, Learning Curve and Outcomes - V A Kumar; Ramanadha Reddy; Vamsi Krishna Yerramneni; Swapnil Kolpakawar; K.S. Vishwa Kumar; Patlolla Pratyusha (Indian Journal of Neurosurgery)
Objective To study the indications, technical nuances, learning curve, and outcomes associated with minimally invasive tubular discectomy of spine (MITDS) and minimally invasive tubular decompression (MITD) using the tubular retractor system and compare the outcomes with open microdiscectomy and open decompression. Materials and Methods All patients who underwent MITDS and MITD received a trial of conservative management for 6 weeks prior to surgery. Patients who had undergone open microdiscectomy and open decompression during the same period were used as controls. Operating time, intraoperative blood loss, preop and postop visual analogue scale (VAS) scores, preop and postop Oswestry disability index (ODI) scores, duration of hospital stay, complications, and need for redo surgery were analyzed. Results Thirty-two patients who underwent MITDS and 8 patients who underwent MITD were compared with an equal number of patients who underwent open microdiscectomy and open decompression, respectively. MITDS and MITD were associated with shorter hospital stay. Short-term pain outcome was better in MITDS and MITD group, although it was not statistically significant in MITD group. Functional outcome measured in terms of ODI at 6 months was not statistically significant between minimally invasive and open procedures. Conclusion Both MITDS and MITD have a significant learning curve and have a distinct advantage of shorter hospital stay. MITDS has the distinct advantage of better short-term pain relief compared with open procedures. For MITD, comparison of short-term pain relief requires a larger sample size. To establish long-term advantages of MITDS and MITD, larger sample size and long-term follow-up are needed.